Los jóvenes escritores hispanoamericanos : literatura y cultura de masas - Szymoniak, Ewelina (Romanica Silesiana)
The presence of materials and structures derived from mass culture is considered one of the distinctive features for South American literature in the post period. However, while more experienced writers (that is those associated with the boom) had been clearly denoting the inferior character of mass culture in comparison to high culture (literature), this distinction started to vanish gradually over the 1990s. This paper is to demonstrate that the dexterity of young South American novelists in exploring the fast culture world (Paz Soldán) can be explained in the light of the theory of literary generations by Kazimierz Wyka. It transpires that the so-called period of rooting in society (Spranger), overlapping the 1970s and 1980s, coincided with a rapid development of mass media in South America. Being the fundamental source of mediated experiences (Giddens), mass media have become a looking glass for the perception of reality and an individual’s identity. This is reflected in the writing of young authors: in Por favor, rebobinar (1994), Alberto Fuguet represents the life of young generation Chileans connected with the mass media world, using its diverse discourses. Key words: South American literature, mass culture, young generation writers.